State of Innovative Leadership of School Administrators under the Pathum Thani Primary Educational Service Area Office 2 - สุภาวิตา, กัญจน์ณิชา; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: (1) examine the innovative leadership of school administrators; (2) compare the innovative leadership of school administrators classified by personal characteristics; and (3) investigate guidelines for developing innovative leadership among school administrators under the Pathum Thani Primary Educational Service Area Office 2. The sample consisted of 314 school administrators and teachers under the Pathum Thani Primary Educational Service Area Office 2, drawn from a population of 1,450 individuals. The sample size was determined using the formula proposed by Taro Yamane (1973). The participants were selected through stratified random sampling and simple random sampling techniques. The research instruments were a questionnaire and an interview form, with a reliability coefficient of 0.986. The statistical methods used for data analysis included frequency, percentage, mean, standard deviation, t-test, F-test, and content analysis.           The results revealed that: 1. The overall state of innovative leadership among school administrators under the Pathum Thani Primary Educational Service Area Office 2 was at the highest level. Among the dimensions, teamwork and participation had the highest mean score followed by the creation of an innovative organizational climate while innovative risk management had the lowest mean score but remained at a high level. 2. Statistically significant differences in innovative leadership of school administrators classified by position status, both overall and across dimensions were at the .01 level. No significant differences were observed by educational attainment or work experience. Differences by school size were significant overall at the .05 level; specifically, visionary leadership for change was statistically difference at the .01 level whereas innovative organizational climate, creativity, and innovative risk management differed in significant statistic at the .05 level. No significant differences were found in teamwork and participatory leadership. 3. Approaches for developing innovative leadership among school administrators were: (1) enhancing competencies in innovative vision and digital, (2) transforming professional development in experiential learning, and (3) establishing a school-based innovation ecosystem.